Characterization of urdbean genotypes for agro-morphological and seed yield traits in Jammu region - Sonali Rajput; Anjani Kumar Singh; Sanjeev Kumar; Vishal Raina; Amrish Vaid; Praveen Singh (Vegetos, 2026)

Morphological and molecular screening of mustard [Brassica juncea (L.) Czern & Coss.] genotypes against Albugo candida (Pers.) Kuntze causing white rust - Sakshi Sharma; Amrish Vaid; Ranbir Singh; R. Nilesh Kumar; Ayushi Sharma; Megha Abrol (Journal of Plant Pathology, 2025)

Tracking soil health and potentially toxic elements (PTEs) across land-use types using physico-chemical, magnetic, and geochemical proxies: a case study from Manipal, Southwestern India - Jai Vishnu Degvekar; Esha Ulhas Gadekar; O. Darshana; Jagath Chand; Vadakkeveedu Narayan Amrish; Jithin Jose; K. Priya; Santhosh Prabhu; Anish Kumar Warrier (Environmental Geochemistry and Health, 2025)
This study investigates spatial variations in soil quality across five distinct land-use types—forest, roadside, agricultural, industrial, and residential—in the Manipal region of southern India. Ten surface soil samples from each land-use category were analysed for physico-chemical properties, geochemical composition, and environmental magnetic parameters to evaluate soil degradation and identify potential pollution sources. Marked variations were observed in electrical conductivity, pH, and salinity, with industrial and roadside soils exhibiting elevated values indicative of anthropogenic impact. Concentrations of potentially toxic elements (PTEs), including Pb, Cr, Cu, and Zn, were significantly higher in roadside and industrial areas, frequently exceeding recommended safety thresholds. Environmental magnetic measurements, such as low-frequency magnetic susceptibility (χ lf ) and frequency-dependent susceptibility (χ fd %), effectively differentiated between anthropogenic and pedogenic magnetic inputs. Principal Component Analysis (PCA) highlighted distinct contamination patterns and revealed strong correlations between magnetic parameters and PTE concentrations. Pollution indices—including the Pollution Load Index (PLI), Enrichment Factor (EF), and Contamination Factor (CF)—identified notable contamination in industrial soils (PLI > 1.3). Overall, the findings underscore increasing environmental pressures on soil systems in rapidly urbanizing regions and demonstrate the value of environmental magnetism as a cost-effective, non-destructive tool for early detection and long-term monitoring of soil pollution. These insights can inform sustainable land management strategies and guide policy frameworks aimed at safeguarding soil health and ecological resilience.

Exploring the potential of semi-synthetic Swertiamarin analogues for GLUT facilitation and insulin secretion in NIT-1 cell lines: a molecular docking and in-vitro study - Satyender Kumar; Prakash Niguram; Vinod Jairaj; Neelam Makwana; Seema Jinagal; Sneha Sagar; Rakesh Kumar Sindhu; Amrish Chandra (Natural Product Research, 2025)

Production and optimization of soybean biodiesel production at fixed temperature 50 °C with RSM and ANN - Sunil Kumar; Vivudh Fore; Jasbir Singh; Ashish Nainwal; Gorav Kumar Malik; Amrish Kumar (Environmental Science and Pollution Research, 2025)

Assessment of genetic variability, correlation, and path coefficient analysis of yield and yield components traits in Urdbean [Vigna mungo (L.) Hepper] - Sonali Rajput; Anjani Kumar Singh; Sanjeev Kumar; Vishal Raina; Amrish Vaid (Vegetos, 2025)

Comparative assessment of anti-ulcer effects: Hydro-ethanolic extract from air-dried ray and disc florets vs essential oil of traditional Tagetes erecta (Asteraceae) in Swiss Albino rats - Amrish Kumar; Vrish Dhwaj Ashwlayan; Ratneshwar Kumar Ratnesh; Jay Singh; Mansi Verma (South African Journal of Botany, 2024)

Exploring bioactive compounds and antioxidant properties of twenty-six Indian medicinal plant extracts: A correlative analysis for potential therapeutic insights - Sachin Kumar; Nutan Chauhan; Bhawna Tyagi; Poonam Yadav; Ashis Kumar Samanta; Amrish Kumar Tyagi (Food and Humanity, 2023)

An environmentally benign oil dispersion/phytoextract system for improved retention upon foliage and control of aphids in spice crops - Smriti Kala; Amrish Agarwal; Krishna Kant; B.K. Mishra; Nisha Sogan; Natish Kumar; Chetan K.D. Jawle; Dipak Kumar Hazara; Jitendra Kumar (Journal of Cleaner Production, 2023)

Assessment of pollution and risks associated with microplastics in the riverine sediments of the Western Ghats: a heritage site in southern India - Kaniyambadi Amrutha; Sachin Shajikumar; Anish Kumar Warrier; Joju George Sebastian; Yamuna Adichinalniravel Sali; Thara Chandran; Sanitha Sivadas; Ravidas Naik; Vadakkeveedu Narayan Amrish; Arun Kumar; Vishnu Unnikrishnan (Environmental Science and Pollution Research, 2022)
There is very little knowledge on microplastic pollution in the Western Ghats (WG), a heritage site in southwest India. To address this, we have studied the spatiotemporal variations of sedimentary microplastics (MPs) from the River Sharavathi, a pristine river in the Western Ghats (WG), southern India. The rich biodiversity in the region makes it relevant to analyse the distribution of this emerging pollutant that is causing harm to the biota and the ecosystem. We analysed the sedimentological and carbon content (organic and inorganic) of these sediments and explored their relationship with MPs. Finally, risk assessment indices such as the Pollution Load Index (PLI), the Polymer Hazard Index (PHI), and the Potential Ecological Risk Index (PERI) were calculated to detect the levels of plastic pollution. The concentration of MPs ranged from 2.5 to 57.5 pieces/kg and 0 to 15 pieces/kg during the pre-monsoon and post-monsoon seasons, respectively. The dip in the MPs’ abundance during the post-monsoon season was due to the extremely high rainfall in the river basin during July–August 2019, which would have entrained the sedimentary MPs and transported them to the coast/Arabian Sea. Smaller MPs (0.3–1 mm) were more abundant than the larger MPs (1–5 mm), mainly due to the breakdown of sedimentary plastics by physical processes. Fragments, films, foams, and fibres were the main categories of MPs, and the main polymers were polyethylene, polyethylene terephthalate, and polypropylene. No significant relationship was observed between the sedimentological properties and microplastics, which may be due to the different physical properties of sediments and microplastics. The PLI, PHI, and PERI indices suggest different contamination levels in the river basin. Based on the PLI scores, all the samples belong to the hazardous level I suggesting minor risk category, and the risk of microplastic pollution falls under the high to hazardous risk category based on the PHI values. The PERI value ranged from 160 to 440 and 40 to 2240 during the pre-monsoon and post-monsoon seasons, respectively. The risk assessment in a region known for its rich biodiversity is crucial, as the data can be used by the district administration to mitigate plastic pollution.

Risk assessment and spatio-temporal distribution of dissolved trace metals in Swarna, Sharavati and Kali estuaries, South-West Coast of India - D’Souza Nishitha; Athiyarath Krishnan Sudheer; Kumar Arun; Vadakkeveedu Narayan Amrish; Gaddam Mahesh; Harikripa Narayana Udayashankar; Keshava Balakrishna (Environmental Science and Pollution Research, 2022)
Trace metals act as a limiting nutrient and prerequisite for primary productivity in marine environments. The distribution of metals in dissolved phase along the salinity gradients of Swarna, Sharavati and Kali estuaries in southwestern India, during post and pre-monsoon seasons, were studied. We have investigated the behaviour of trace metals in the estuarine environment and their extent of impact on human health and ecosystem. The study revealed, non-conservative behaviour of dissolved Mn, Fe, Ni, Cd and Co in the estuaries. Whereas Cu behaved non-conservatively in post-monsoon and conservatively in pre-monsoon seasons. Risk assessment studies revealed that higher chronic daily intake (CDI) in humans, through dermal pathway, in Swarna and Sharavati estuaries during post-monsoon, whereas it was during pre-monsoon season in the Kali estuary. Hazard Index values for the studied metals in adults and children are below risk thresholds, though children are more prone to health risk through the dermal pathway.

Autochthonous Limosilactobacillus reuteri BFE7 and Ligilactobacillus salivarius BF17 probiotics consortium supplementation improves performance, immunity, and selected gut health indices in Murrah buffalo calves - Vinay Venkatesh Varada; Amrish Kumar Tyagi; Praveen Sivakumara Banakar; Asit Das; Nitin Tyagi; Rashmi Hogarehalli Mallapa; Sachin Kumar (Veterinary Research Communications, 2022)

Study of trace metal contamination and ecological risk assessment in the sediments of a tropical river estuary, Southwestern India - D’Souza Nishitha; Vadakkeveedu Narayan Amrish; Kumar Arun; Anish Kumar Warrier; Harikripa Narayana Udayashankar; Keshava Balakrishna (Environmental Monitoring and Assessment, 2022)
The present study aims to assess the extent of trace metal pollution in the sediments of Sita-Swarna estuary, west coast of India, and investigate their possible ecological risk on the aquatic environment. The sediment cores were analyzed for sand, silt, clay, organic carbon, and trace metals (Al, Fe, Mn, As, Cd, Co, Zn, Pb, Ni, Cr, and Cu) at 2-cm intervals. The study revealed that sediments have deposited in relatively violent to very violent hydrodynamic energy conditions. Factor analysis indicated that the metal distribution is mainly controlled by Fe–Mn oxyhydroxides and organic carbon. Further, the geochemical approach, pollution indices, and statistical evaluation revealed moderate pollution in the catchment. From an ecotoxicological perspective, the estimated risk index (RI) value was found to less than 150, indicating low risk for aquatic life. Thus, this baseline study would help to adopt strategies in pollution control and protect the fragile marine environment.

Supplementation of Aloe vera extract in lactating goats’ diet: effects on rumen fermentation efficiency, nutrient utilization, lactation performance, and antioxidant status - P. S. Banakar; Sachin Kumar; V. V. Vinay; Sonam Dixit; Nitin Tyagi; Amrish Kumar Tyagi (Tropical Animal Health and Production, 2021)

Lectin-Conjugated Clarithromycin and Acetohydroxamic Acid-Loaded PLGA Nanoparticles: a Novel Approach for Effective Treatment of H. pylori - Sunil K. Jain; Tanweer Haider; Amrish Kumar; Akhlesh Jain (AAPS PharmSciTech, 2016)

Dietary Inorganic Chromium in Summer-Exposed Buffalo Calves (Bubalus bubalis): Effects on Biomarkers of Heat Stress, Immune Status, and Endocrine Variables - Muneendra Kumar; Harjit Kaur; Rijusmita Sarma Deka; Veena Mani; Amrish Kumar Tyagi; Gulab Chandra (Biological Trace Element Research, 2015)

Body Condition, Energy Balance and Immune Status of Periparturient Murrah Buffaloes (Bubalus bubalis) Supplemented with Inorganic Chromium - Rijusmita Sarma Deka; Veena Mani; Muneendra Kumar; Zade Satish Shiwajirao; Amrish Kumar Tyagi; Harjit Kaur (Biological Trace Element Research, 2014)

Energy Metabolites, Lipid Variables and Lactation Performance of Periparturient Murrah Buffaloes (Bubalus bubalis) Fed on Diet Supplemented with Inorganic Chromium - Satish Zade; Veena Mani; Rijusmita Sarma Deka; Muneendra Kumar; Harjit Kaur; Neelam J. Kewalramani; Amrish Kumar Tyagi (Biological Trace Element Research, 2014)

Effect of Feeding Inorganic Chromium on Growth Performance, Endocrine Variables, and Energy Metabolites in Winter-Exposed Buffalo Calves (Bubalus bubalis) - Muneendra Kumar; Harjit Kaur; Amrish Kumar Tyagi; Neelam J. Kewalramani; Veena Mani; Rijusmita Sarma Deka; Vijay Kumar Sharma; Gulab Chandra; Ajay Kumar Dang (Biological Trace Element Research, 2013)

Assessment of Chromium Content of Feedstuffs, Their Estimated Requirement, and Effects of Dietary Chromium Supplementation on Nutrient Utilization, Growth Performance, and Mineral Balance in Summer-Exposed Buffalo Calves (Bubalus bubalis) - Muneendra Kumar; Harjit Kaur; Amrish Tyagi; Veena Mani; Rijusmita Sarma Deka; Gulab Chandra; Vijay Kumar Sharma (Biological Trace Element Research, 2013)